The equilibrium model of relationship maintenance. [article]. - Murray, Sandra L.; Holmes, John G.; Griffin, Dale W.; Derrick, Jaye L.
A new equilibrium model of relationship maintenance is proposed. People can protect relationship bonds by practicing 3 threat-mitigation rules: trying to accommodate when a partner is hurtful, ensuring mutual dependence, and resisting devaluing a partner who impedes one?s personal goals. A Longitudinal study of newlyweds revealed evidence for the equilibrium model, such that relationship well-being (as indexed by satisfaction and commitment) declining from its usual state predicted increase threat-mitigation; in turn, increasing threat mitigation from its usual state predicted increased relationship well-being. Longitudinal findings further revealed adaptive advantage to uncertain trust. First, the match between trust and partner-risk predicted the trajectory of threat mitigation over time. People who hesitated to trust a high-risk partner became more likely to mitigate threats over 3 years, but people who hesitated to trust a safe partner became less likely to mitigate threats. The match between threat mitigation and partner-risk also predicted when being less trusting eroded later relationship well-being. Namely, when women paired with high-risk partners became more likely to mitigate threats, being less trusting at marriage lost its capacity to erode later relationship well being. - - (from the authors)